Structure Design and Mechanical Analysis of Bionic Pipe-climbing Robot based on Metamorphic Mechanism - Zihan Jin; Yu Hou; Qiang Wang; Wei Sun (Jixie chuandong)
The design of the existing pipe-climbing robot often focused on adaptability，obstacle climbing ability and load capacity，which cannot meet the comprehensive requirements of all aspects of performance in the actual operation. Therefore，based on the bionics theory and the metamorphic theory，a new kind of pipe-climbing robot is designed，which has the performance of adaptability，obstacle climbing ability and load capacity. The static models of the metamorphic grippers and the robot are established，and the gripper force and the friction force of the foot are analyzed under three conditions. The gait of climb in the vertical pipe robot climbing and flip movement is designed，and based on the Adams，pipe-climbing robot kinematics and dynamics simulation are analyzed. The clamping force and the friction force in the process of climbing pipe change rule is obtained. And the stability of the robot in the line movement is realized. Therefore the correctness of the structure design and mechanics model of the robot is verified.